2021
DOI: 10.1016/j.heliyon.2021.e07969
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral characterization, lethal dose (LD50) and acute toxicity studies of 1,4-Bis(imidazolylazo)benzene (BIAB)

Abstract: Synthesis, spectral characterization, lethal dose (LD 50 ) and acute toxicity studies of 1,4-Bis(imidazolylazo)benzene (BIAB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…For free ligand (DMPDE), the UV‐Vis. spectra showed an absorption maximum at 401 nm (24937.66 cm −1 ), which was attributed to an intramolecular charge transfer (n→π*) transition between the azo side chain and carbonyl moiety [46] . While the absorption band at the UV region 240 nm (41666.67 cm −1 ), was assigned for intermolecular charge transfer (π→π(* transition of π‐systems (phenolic moiety and benzene moiety), respectively (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For free ligand (DMPDE), the UV‐Vis. spectra showed an absorption maximum at 401 nm (24937.66 cm −1 ), which was attributed to an intramolecular charge transfer (n→π*) transition between the azo side chain and carbonyl moiety [46] . While the absorption band at the UV region 240 nm (41666.67 cm −1 ), was assigned for intermolecular charge transfer (π→π(* transition of π‐systems (phenolic moiety and benzene moiety), respectively (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…Results confirmed that the azo dye ligand DMPDE behaves as a bidentate and coordinates to the metal ion via, the nitrogen atom of the azo group which is the farthest of the acetophenone moiety and oxygen phenolic for benzene moiety. Tetrahedral environment is suggested for Ag(I) metal complex [Ag(DMPDE)(H 2 O) 2 ] [23,25,46,71] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3.9 Loaded ZnO-NPs and HCQ properties on a κC-Sa/ZnO composite It is clear that incorporating hydroxychloroquine into the κC-Sa/ZnO matrix improves the antibacterial characteristics of that gel versus both Gram-positive and Gram-negative types of bacteria, which can be a direct outcome of stopping the production of protein by those bacteria (Kyhoiesh et al 2021). Regardless of ZnO-NPs concentration, adding hydroxychloroquine has a favorable effect on the antibacterial as well as gel fraction.…”
Section: Drug Loading In Vitromentioning
confidence: 99%